Aplicação de Programas de Exercício Físico para a Terceira Idade em Realidades Distintas - Relatório de Estágio - Maria do Rosário Lima Terroso (2017)
Population aging is one of the most significant trends of the 21st century, with this increase in the elderly population, it is expected that many professionals dealing with this age group will be concerned to understand and study the variables that influence healthy and balanced aging, with an adoption of habits that contribute to global health.This report aims to record and analyze the work developed in the last year where I completed the internship with an elderly population in different places with different realities.The present internship report advocates the construction of a physical exercise program based on the physical capacities of the subjects, in the context in which it is inserted and available in available resources: a multicomponent training program (maintenance gymnastics) for the institutionalized elderly and for the control group of the faculty, and another training of muscular endurance (bodybuilding) for the non-institutionalized group. The training programs last 9 months, with 1 to 2 weekly sessions of about 60 minutes. The results showed that at the end of the physical exercise program for each of the groups, significant improvements were achieved in most of the parameters evaluated, consequently an improvement in the physical and functional fitness of the elderly and the effectiveness of the application of physical exercise programs to promote healthier and more active aging.